"Justice in the World" at 50: A Call to Action Worthy of Recovery. Issue 2 (15th March 2022) - Procario-Foley, Carl B.
Abstract: The Synod of Catholic Bishop's 1971 document, "Justice in the World, " articulates boldly that "action on behalf of justice is a constitutive dimension of the preaching of the Gospel." Fifty years old, it is timely to assess this document today especially as religious educators address the many forms of inequality in the world. Examining gaps in the church's approach to racial justice, this paper maintains that lessons learned from the past 50 years might guide future implementation of this important teaching. The paper proposes both activist and contemplative practices to recover the boldness and passion of "Justice in the World."